Water: Asia’s New Battleground - Chellaney , Brahma; Aneet (Gyan Management Journal, 2013)
The battles of yesterday were fought over land; those of today are over energy. But the battles of tomorrow may be over water. Nowhere is that danger greater than in water-distressed Asia.Water stress is set to become Asia’s defining crisis of the twenty-first century, creating obstacles to continued rapid economic growth, stoking interstate tensions over shared resources, exacerbating long-time territorial disputes, and imposing further hardships on the poor. Asia is home to many of the world’s great rivers and lakes, but its huge population and exploding economic and agricultural demand for water make it the most water-scarce continent on a per capita basis. Many of Asia’s water sources cross national boundaries, and as less and less water is available, international tensions will rise. The potential for conflict is further underscored by China’s unrivalled global status as the source of trans boundary river flows to the largest number of countries, as it declines to enter into water-sharing or cooperative treaties with these states, even as it taps the resources of international rivers.